PENYULUHAN PENTINGNYA SARAPAN PAGI BAGI SISWA SEKOLAH DASAR NEGERI 2 TIAL KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Michran Marsaoly; Deby Nur Fajni; Santi Aprilian Lestaluhu (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2021)
School children are strategic targets in providing information, education and instilling a healthy lifestyle from an early age because elementary school-aged children are easy to accept input and change. Another thing to consider is that children experience a period of rapid growth. This period would run well if it was supported by good nutrition, fulfilled and balanced. Education and information on balanced nutrition need to be conveyed to increase knowledge of balanced nutrition and equip children in their age of growth and development. The purpose of the activity is to increase school children's knowledge about the importance of the benefits of breakfast for school children. This community service is carried out by the method of counselling/lectures using slide presentation media. The activity continued with the distribution of leaflets to all participants and the installation of posters in schools. The measuring knowledge before counselling and distributing leaflets obtained an average value of 64, with the lowest score being 14 and the highest being 90. In comparison, the average score for knowledge value after counselling and distributing leaflets was 70, with the lowest score being 28 and the highest 100. Extension activities and distribution of leaflets about the importance of breakfast can be carried out at SDN 2 Tial according to the planned time with a target number of 115 people. There was an increase in students' knowledge about the importance of breakfast after being given counselling, distributing leaflets, and installing posters.